Comparative Analysis of Vascular Density in the Femoral Head Ligament of the Dog, Sheep, and Goat - Stanard, Imani; Almhanna, Hazem; Al-Mahmodi, Aqeel Mohsin Mahdi; Kilroy, David; Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports, 2026)
Background: The ligament of the head of the femur (ligamentum teres) is an intra-articular structure that contributes to hip joint stability and serves as a potential conduit for vascular supply to the femoral head. Despite its recognised anatomical presence across mammalian species, its vascular capacity and functional significance remain incompletely understood. This study aimed to comparatively evaluate vascular density within the ligament of the femoral head in adult dog, sheep, and goat, and to determine whether a relationship exists between ligament length and vascular characteristics. Materials and Methods: Nine cadavers (three specimens each of adult dog, sheep, and goat) were examined. Ligament length was measured macroscopically, and selected samples were processed for histological analysis using haematoxylin and eosin staining. High-resolution images were analysed using ImageJ software to quantify blood vessel area and vascular density. Statistical analysis was performed using one-way ANOVA followed by Bonferroni post hoc testing, with significance set at p<0.05. Results: Ligament length ranged from 13-22 mm in dogs and 20-22 mm in both sheep and goats. No correlation was identified between ligament length and blood vessel area. However, significant interspecies differences in vascularity were observed. Goats exhibited a significantly greater mean blood vessel area (47,025.58 μm²) and higher vascular density compared to both dogs (10,289.43 μm²) and sheep (5,806.94 μm²) (p<0.05), while no significant difference was found between dogs and sheep. The ratio of vessel area to density was not significantly different among species. Conclusion: These findings demonstrate that vascular characteristics of the ligament of the femoral head vary between species and are not dependent on ligament length. The increased vascular density observed in goats suggests a potentially greater contribution to femoral head perfusion. This study highlights the importance of vascular density as a relevant parameter in understanding ligament function and may have implications for the pathophysiology and treatment of conditions associated with compromised femoral head blood supply.
Keywords: Comparative anatomy; Femoral head perfusion; Histological analysis; Ligament of the; femoral head; Vascular density